1996
DOI: 10.1007/bf00262803
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in biomechanical properties of the Achilles tendon in rabbits

Abstract: We investigated age-related changes in the mechanical properties of rabbit Achilles tendon. The animals used were immature (age 3 weeks, body mass 380 g), young adult (age 8-10 months, body mass 4.1 kg) and old (age 4-5 years, body mass 5.1 kg) rabbits. The cross-sectional area of the tendon increased with growth and the tensile strength of the young adult [67.3 (SEM 4.2) MPa] and old [66.7 (SEM 3.8) MPa] tendon was significantly higher than that of the immature tendon [23.9 (SEM 3.8) MPa]. However, there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 23 publications
4
72
0
6
Order By: Relevance
“…ULF increased between 6 and 16 weeks of age and then decreased in the older animals ( Table 2). This trend is similar to that described previously for age-related failure properties in tendons and ligaments (31,32). Two-way ANOVA showed that there was no significant difference in this structural property between DH and BS2 animals.…”
Section: Biomechanicssupporting
confidence: 90%
“…ULF increased between 6 and 16 weeks of age and then decreased in the older animals ( Table 2). This trend is similar to that described previously for age-related failure properties in tendons and ligaments (31,32). Two-way ANOVA showed that there was no significant difference in this structural property between DH and BS2 animals.…”
Section: Biomechanicssupporting
confidence: 90%
“…Recent reports demonstrate that young human tendons respond to physical activity by increasing tendon size, which is accompanied by altered functional mechanical properties Seynnes et al 2009). In animal models, aging is associated with an increase in tendon cross-sectional area (Nakagawa et al 1996;Birch et al 1999), and in humans, the Achilles tendon, but not the patellar tendon, appears to undergo hypertrophy with aging (Magnusson et al 2003;Carroll et al 2008). In the present study, we found a greater crosssectional area of the patellar tendon in endurance athletes, which by definition resulted in a lower tendon stress for a given load.…”
Section: Tendon Dimensionssupporting
confidence: 55%
“…One study suggests that aging produces stiffer and stronger tendons [50], but other investigations led to the opposite conclusion [44,54] or showed no effect of aging on most of the mechanical properties of the tendon [16]. In animals, tenocyte metabolism changes with increasing age [13], and these changes are accompanied by morphologic changes [6].…”
Section: Introductionmentioning
confidence: 99%